Insecticidal properties of an alkaloid from Alstonia boonei de wild - Nathaniel, O.O.; Benjamin, I. I.; Manuele, T. (2010)
The insecticidal properties of the alkaloid obtained from Alstonia boonei De Wild stem bark was tested against the maize stem borer, Sesamia calamistis Hampson in a laboratory bioassay. Less than one day old (less than 24 h after hatching) S. calamistis larvae were reared on artificial diet treated with the alkaloid at a rate of 0.00125 %, 0.00100 %; 0.00050 %, 0.00025 %, and 0.00000 % (Control). There was no significant difference between the treatments in the survival of the larvae (range 66.67 % to 86.67 %). at 15 days after introduction (DAI). There were significant differences (P < 0.05) in the wet and dry weights of these larvae, which ranged from 25.50 mg in the diet containing 0.00125 % of the alkaloid to 36.30 mg in the 0.00050 % and 5.90 mg in the 0.00125 % to 8.80 mg in the 0.00025 %, respectively. The natural response rate C, (OPTC) for the larval survival at 15 DAI was 0.25. Percentage pupation was significantly higher in the Control (80 %) compared with the rest treatments (range 40 – 53.33 %). Pupal weight was significantly higher in the Control (213.67 mg) compared with the 0.00100 % treatment (137.83 mg). The natural response rate C, (OPTC) for pupation was 0.42 with an LD50 of 0.02662 %. While all the pupae from the Control successfully emerged into the adults, percentage adult emergence for pupae from other treatments ranged from 0.00 to 35.00 %. Various stages of unsuccessful adult emergence were observed in the treatments containing the alkaloid. Total developmental period ranged from 45 days in the 0.00025 % to 58 days in the 0.00125 %. These results show a very high level of insecticidal property of A. boonei stem bark alkaloid against S. calamistis. We believe that this alkaloid can play a major role in the management of this insect and similar insect pests of tropical crops.